Development of a complex multicomponent microstructure on commercial carbon-silicon grade steel by governing the phase transformation mechanisms to design novel quenching and partitioning processing - Carvalho, Felipe M.; Centeno, Dany; Tressia, Gustavo; Avila, Julian A. [UNESP]; Cezario, Fabiano E.M.; Márquez-Rossy, Andrés; Ariza, Edwan A.; Masoumi, Mohammad (Elsevier, 2022)
The constant demand for increasing the strength without ductility loss and production cost encourages industrial and academic societies to propose novel heat treatment processing of commercial steel grades. To improve the mechanical properties of commercial spring steel, a novel quenching and partitioning (Q&P) processing was designed to deliver a complex and desirable nanostructured multicomponent microstructure by controlling the carbon partitioning kinetics. Furthermore, the partitioning of excessive carbon from saturated martensite into untransformed austenite enhances the formation of transition carbides during tempering between 130 and 280 °C. Electron microscopy confirmed a complex multicomponent structure containing BCC tempered lath combined with retained austenite and nanocarbides particles within the tempered laths. Such multicomponent lath-type structure obtained by designed Q&P heat treatment on commercial carbon-silicon spring steel revealed localized mechanical resistance varying from 4.92 GPa for the QP-220-375-400 to 8.22 GPa for the QP-220-325-400 samples determined by nanoindentation test. Moreover, the tensile test showed high ultimate tensile strength and a yield strength up to 1400 MPa and 975 MPa, respectively, in the QP-220-375-400 sample due to a set of complex multicomponent lath-type refined structures designed by Q&P coupled with bainitic transformation, with good strain to fracture (∼0.12%).
Keywords: Boundaries; Crystal orientation; Kernel average misorientation; Lattice distortion; Nanoparticles